Climate change impedes plant immunity mechanisms - Son, Seungmin; Park, Sang Ryeol (Frontiers in Plant Science, 2022)
Rapid climate change caused by human activity is threatening global crop production and food security worldwide. In particular, the emergence of new infectious plant pathogens and the geographical expansion of plant disease incidence results in serious yield losses of major crops annually. Since climate change has accelerated recently and is expected to worsen in the future, we have reached an inflection point where comprehensive preparations to cope with the upcoming crisis can no longer be delayed. Development of new plant breeding technologies including the CRISPR/Cas9 system offers the opportunity to mitigate the effects of the changing climate. Therefore, understanding the effects of climate change on plant innate immunity and identification of elite genes conferring disease resistance is crucial for the engineering of new crop cultivars and plant improvement strategies. Here, we summarize and discuss the effects of major environmental factors such as temperature, humidity, and carbon dioxide concentration on plant immunity systems. This review provides a strategy for securing crop-based nutrition against severe pathogen attacks in the era of climate change.